The benefit of Cyctocele repair in improving the symptoms of Stress urinary incontinence - رسلان فرح; حسن صالح; جهاد أيوب (Latakia University Journal -Medical Sciences Series, 2022)
The urinary and reproductive tracts are fundamentally anatomically and genetically linked from the early stages of their development , the bladder is placed directly above the front wall of the vagina and the urethra merges into it , and both of these structures, such as other compositions at the bottom of the pelvis, are at risk, During pregnancy and childbirth, about 40-50% of women with pelvic organ prolapse have stress urinary incontinence, pelvic organ prolapse affects millions of women as about 200,000 surgical procedures are performed annually to treat the prolapse in the United States. About 11-19% of women aged 70-80 will undergo surgery to treat the prolapse and 30% of these women require additional surgery, stress urinary incontinence is a common problem in women and its prevalence is estimated at about 17-45% of adult women. But less than half of women with incontinence seek health care because of the sensitivity of the subject.